Sustainable Solutions for Pollutants Removal with a Hybrid Multifunctional Adsorbent Based on Recycled Expanded Glass - Ali Abdussalam Almazoug; Slavko Mijatov; Marija M. Vuksanović; Milutin Milosavljević; Asifa Jasim Mohammed Mohammed; Milena D. Milošević; Aleksandar Marinković; Mirjana Bartula (Applied Sciences)
The removal of the As(V) and Iprodione fungicide onto EGS@APTES-GT, obtained by amino-modified expanded glass spheres (EGS) modified with goethite, was studied in this work. Material characterization was performed using SEM/EDS, XRD, and FTIR techniques. The adsorption capacities of 51.01 and 94.28 mg g−1, for As(V) and Iprodione removal at 25 °C, respectively, were achieved. A kinetic study indicated lower intraparticle diffusional transport resistance. Physisorption is the dominant mechanism for Iprodione removal, while surface complexation is for As(V). The disposal of effluent water after five adsorption–desorption cycles was attained through Iprodione photocatalytic degradation and arsenate precipitation. Exhausted EGS@APTES-GT, processed by goethite acidic dissolution and grinding, was used as a reinforcing filler in composites production based on commercial unsaturated polyester resin (UPe). An improvement in the mechanical properties was observed, with a gradual increase in the tensile strength, reaching a maximum of 25.9% for UPe with 10 wt.% of ground exhausted adsorbent compared to pure UPe. The overarching concept is defined by the aspiration to develop technologies that address all output flows of advanced processes. Thus, the combination of wastewater treatment technologies and the production of potentially marketable composites successfully achieved both a low environmental impact and the implementation of a circular economy.